Postbiotic Gamma-Aminobutyric Acid and Camel Milk Intervention as Innovative Trends Against Hyperglycemia and Hyperlipidemia in Streptozotocin-Induced C57BL/6J Diabetic Mice - Amro Abdelazez; Amro Abdelazez; Amro Abdelazez; Garsa Alshehry; Eman Algarni; Huda Al Jumayi; Heba Abdel-Motaal; Heba Abdel-Motaal; Xiang-Chen Meng (Frontiers in Microbiology, 2022)
Diabetes is a serious disease that threatens human health worldwide. The study hypothesis is to investigate the novel trends that may aid in the prevention of diabetic complications. Camel milk was presented as traditional functional food, and Lactobacillus brevis KLDS1.0727 and KLDS1.0373 strains were shown to synthesize postbiotic Gamma-aminobutyric acid as a potential food additive, which can therapeutically intervene against hyperglycemia and hyperlipidemia in streptozotocin-induced C57BL/6J mice. During a four-week timeframe, body weight and postprandial blood glucose levels were monitored. Post-euthanasia, blood plasma was obtained to investigate hyperlipidemia, insulin concentrations, liver, and renal functions. The liver, pancreas, kidney, and spleen underwent histopathological examinations. The results demonstrated that KLDS1.0727 and KLDS1.0373 (LACS1, LACS2) and camel milk treatments all had a significant influence on hypoglycemic activity, as evidenced by reduced postprandial blood glucose levels. LACS1, LACS2, and camel milk therapy significantly reduced blood hypolipidemic, and some liver enzymes such as (alanine aminotransferase and aspartate transaminase) levels. Therefore, we recommend consuming camel milk regularly and expanding its use with fermented foods containing L. brevis, one of the probiotics capable of producing gamma-aminobutyric acid (GABA) as future food additives that can improve human health and reduce the prevalence of several diseases disorders.